Graph Trace Analysis: An object-oriented power flow, verifications and comparisons - Tbaileh, Ahmad; Jain, Himanshu; Broadwater, Robert; Cordova, Jose; Arghandeh, Reza; Dilek, Murat (Electric power systems research, 2017)
•This paper describes an alternative approach for power systems computations and used to solve the power flow problem.•Implementation of Kirchhoff voltage (KVL) and current (KCL) laws is included. The GTA power flow algorithm is compared to other power flow solvers.•Power flow solutions of hybrid, or integrated transmission and distribution models, are needed, including the ability to solve detailed substation models and even downtown network models.•GTA algorithms can solve multi-domain models, and that the same algorithm can be used to analyze across different engineering domains.•The implementation of GTA relies on traces, which allows GTA algorithms to be naturally distributed across multiple processors by just distributing the model. This paper presents an alternative approach to power system computations, Graph Trace Analysis (GTA), and applies this approach to solving the power flow problem. GTA is derived from the Generic Programming Paradigm of computer science, and uses topology iterators to move through components in a model and perform calculations. The implementation of KVL and KCL in GTA is described. The GTA based power flow algorithm is shown to solve IEEE standard transmission models, IEEE standard distribution models, and integrated transmission and distribution models (hybrid models) constructed from modifying IEEE standard models. Comparisons with widely used, primarily matrix based, power flow algorithms are provided. Two advantages that GTA brings are the separation of system equations from component equations and the ability to distribute calculations across processors.